2019
DOI: 10.1111/1750-3841.14800
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profiling and Consumer Acceptance of Pasta, Bread, and Granola Bar Fortified with Dried Olive Pomace (Pâté): A Byproduct from Virgin Olive Oil Production

Abstract: An olive pomace (pâté) obtained from virgin olive oil production, was used for the fortification of pasta, bread, and granola bar. For each food, a control (without pâté) and a fortified sample (with pâté, 7% in pasta and 5% in bread and granola bar) were manufactured. Descriptive analysis showed that pâté strongly affected the appearance of pasta and bread and increased the bitterness of bread and granola bar but not pasta. Granola bar was less affected in general, likely because of its higher ingredient comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
4
36
0
1
Order By: Relevance
“…When 6% of the flour were replaced with cellulose,significant drops in the values of all the sensory characteristics were observed in the resulting bread. Our results are similar to that presented by Cecchi, et al (2019) for pasta, bread, and granola bar fortified with olive pomace. Cedola et al 2019found that addition of dry olive paste flour to the bread also slightly interfered with the network formation, thus influencing the final bread bubbles that were considered more acceptable in the control samples than in the enriched bread.…”
Section: Sensory Evaluation Of Toast Bread Samples Fortified With Olisupporting
confidence: 91%
“…When 6% of the flour were replaced with cellulose,significant drops in the values of all the sensory characteristics were observed in the resulting bread. Our results are similar to that presented by Cecchi, et al (2019) for pasta, bread, and granola bar fortified with olive pomace. Cedola et al 2019found that addition of dry olive paste flour to the bread also slightly interfered with the network formation, thus influencing the final bread bubbles that were considered more acceptable in the control samples than in the enriched bread.…”
Section: Sensory Evaluation Of Toast Bread Samples Fortified With Olisupporting
confidence: 91%
“…Finally, dried olive pomace was added to egg pasta, and was evaluated in terms of sensory profile and the preference of consumers 74 . The enriched pasta differed from the control mainly with regard to color and evenness of color, as well as in terms of an ‘eggy’ flavor, which decreased, and olive oil, earthy, and wheat flavors, which increased.…”
Section: Application Of Olive Pomace or Extracted Functional Compoundmentioning
confidence: 99%
“…Other authors 74 assessed the sensory profiling of bread enriched with dried olive pomace. Fortification did not affect the external color but did affect the internal color, which became grayer and darker.…”
Section: Application Of Olive Pomace or Extracted Functional Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that a growing group of consumers is interested in enriched food products of improved nutritional values [ 47 ]. Moreover, some studies indicated that proper labeling and marketing of the fortified products can positively influence acceptance of these products through building positive expectations [ 59 ].…”
Section: Discussionmentioning
confidence: 99%